Environmental risk factors and prevention strategies for colorectal cancer - He Dongqiang; Zhu Weijing; Li Xueliang; Zhang Yalan; Liu Fan; Li Yumin (生物医学转化, 2025)
Colorectal cancer(CRC) is one of the cancers with high incidence and mortality rates globally. Its occurrence is closely related to various environmental risk factors such as dietary habits, lifestyle, living environment, and gut microbiota. This article reviews the impact of these factors on the initiation and progression of colorectal cancer and explores corresponding prevention strategies and future research directions, aiming to provide guidance for early prevention and intervention of colorectal cancer.